EFFECTS OF THREE POSITIVE LIFE SKILLS ON IN-SCHOOL ADOLESCENTS DELINQUENT BEHAVIOUR OF TRUANCY IN PUBLIC SECONDARY SCHOOLS IN IBADAN METROPOLIS, NIGERIA (2015)
Curbing truancy among in-school adolescents in public secondary schools in Nigeria had attracted much attention from stakeholders. Efforts made by government, schools and families to check such behaviour have not produced the desired results, thus necessitating the introduction of positive-life skills interventions. However, literature has shown a relatively low trend in previous studies utilizing positive life skills. Previous studies on positive life skills focused on hardened criminals, run-away boys and prisoners with little attention given to truant in- school adolescents in Ibadan metropolis. This study, therefore, examined the effects of three positive life skills (moral reasoning, social adjustment and study skills) on adolescence delinquent behaviour of truancy in public secondary schools in Ibadan metropolis. It further examined the moderating effects of gender and socio-economic status. The study adopted a pretest-posttest, control group, quasi experimental design, using a 4x2x3 factorial matrix. Eight co-educational public secondary schools in Ibadan were purposively chosen, while simple random sampling technique was used to select 480 Senior Secondary I students (comprising 240 males and 240 females between the ages of 13-19) with a history of truancy. Participants were randomly assigned to moral reasoning, social adjustment, study skills and control groups. Treatment lasted six weeks. Instruments used were: moral reasoning intervention scale, social adjustment scale and study skills intervention scale. These were complemented with four sessions of focus group discussion with some of the participants. Seven hypotheses were tested at 0.05 level of significance. Data were analyzed using ANCOVA, MCA and Scheffe posthoc test. There was a significant main effect of positive life skills on truancy reduction among in-school adolescents in Ibadan (F(3, 405) = 48.67, ƞ2= 0.24). Participants in the social adjustment group had a higher posttest mean score (ẋ = 66.83) than moral reasoning (ẋ= 65.44), study skills (ẋ= 64.56) and control (ẋ= 61.30) groups. There were no significant main effects of gender and socio-economic status on truancy reduction. There was also a significant interaction effect of treatment and gender on truancy reduction (F(3,471) = 5.17, ƞ2=0.03) with gender accounting for 9.6% in the variation of truancy reduction. However, there were no significant interaction effects of socio-economic status and treatment, and gender and socio-economic status on truancy reduction. There was no significant three-way interaction effect of treatment, gender and socio-economic status on truancy reduction. Moral reasoning skills, social adjustment skills and study skills enhanced truancy reduction among in-school adolescents in public secondary schools in Ibadan metropolis. Therefore, these three positive life skills should be taught as school subjects to the secondary school students. The students would increase in knowledge and be able to think rightly, do the right thing at the right time in order to avoid wrong action that can encourage punishment, avoidance of school and truancy. The students would be free to express themselves freely in an environment void of intimidation and biases, which would lead to the realization of students’ internal attributes and ability to do well in class for academic achievement. The students would also know the methodology of studying well, when, how and what to study. Reading ahead of the class, not only when examinations are approaching, but all the time. The act of reading and studying well encourage students to do well in class, pass examinations to become school achievers.